Pemantauan Keanekaragaman Hama dan Musuh Alami Tanaman Ubi Jalar dengan Pitfall Trap - Apriliyanto, Eko; Suhastyo, Arum Asriyanti (Proceedings Series on Physical & Formal Sciences, 2021)
The abundance of pest and natural enemy populations on a land can be given in the diversity and abundance of feeding sources and other available resources. The purpose of this study was to determine the diversity of pests and natural enemies of sweet potato plants. Research on land with three types of sweet potatoes, namely yellow sweet potatoes with narrow leaves, yellow sweet potatoes with broad leaves, and sweet potatoes with white leaves. Around the research area are long beans, papaya, guava, soursop, and durian. Sampling of pests and natural enemies by using a pitfall trap. The data analyzed was in the form of the Shannon-Weaver (H’) diversity index. The index of pest diversity of the order Coleoptera on narrow-leaved yellow sweet potato, broad-leaved yellow sweet potato, and white sweet potato was 0,160; 0,1270; and 0,1300. The index of pest diversity of the order Orthoptera on narrow-leaved yellow sweet potato, broad-leaved yellow sweet potato, and white sweet potato was 0,3585; 0,3599; and 0,3632. The index of pest diversity of the order Hemiptera on narrow-leaved yellow sweet potato, broad-leaved yellow sweet potato, and white sweet potato was 0,0635; 0,0771; and 0,1300. Diversity index of natural enemies of the order Araneae on narrow-leaved yellow sweet potato, broad-leaved yellow sweet potato, and white sweet potato 0.2180; 0.3061; and 0.2705. The three sweet potato fields had a low diversity index.